Occupational disease monitoring by the Korea Occupational Disease Surveillance Center: a narrative review - Dong-Wook Lee; Inah Kim; Jungho Hwang; Sunhaeng Choi; Tae-Won Jang; Insung Chung; Hwan-Cheol Kim; Jaebum Park; Jungwon Kim; Kyoung Sook Jeong; Youngki Kim; Eun-Soo Lee; et al. (The Ewha Medical Journal)
This review examines the challenges associated with occupational disease surveillance in Korea, particularly emphasizing the limitations of current data sources such as the Industrial Accident Compensation Insurance (IACI) statistics and special health examinations. The IACI system undercounts cases due to its emphasis on severe diseases and restrictions on approvals. Special health examinations, although they cover a broad workforce, are constrained by their annual scheduling, which leads to missed acute illnesses and subclinical conditions. The paper also explores the history of occupational disease surveillance in Korea, highlighting the fragmented and disease-specific approach of earlier systems. The authors introduce the newly established Korea Occupational Disease Surveillance Center (KODSC), a comprehensive nationwide system designed to gather, analyze, and interpret data on occupational diseases through a network of regional centers. By incorporating hospital-based surveillance and focusing on acute poisonings and other sentinel events, the KODSC aims to overcome the limitations of previous systems and promote collaboration with various agencies. Although it is still in the early stages of implementation, the KODSC demonstrates potential for improving data accuracy and contributing valuable insights for public health policy.